Silencing cortical activity during sound-localization training impairs auditory perceptual learning - Victoria M. Bajo (Nature Portfolio, 2019)
Sensory circuits can adapt flexibly to changes in inputs yet the neural mechanisms related to experience dependent plasticity are not well understood. Here, the authors use optogenetic approaches in ferrets to show that suppression of auditory cortex during sound localization training can affect learning.